Study of quick diffusion of Fe on α-Zr by sectioning and LIBS techniques - Lucía, Andrés (2020)
Zirconium and its alloys are widely used in nuclear industry (nuclear fuel cladding tubes, structural materials, etc.) for its adequate properties under hostile conditions (corrosive environment, radiation damage, etc.) in the core of nuclear reactors. In normal operating conditions, these materials present an important density of grain and interphase boundaries which act as quick paths for the movement of matter and can be in structural contact with Fe based alloys. The movement of fast diffusing elements (Fe, Co, Cr, Ni) in these short-circuit paths in Zr alloys [1] can produce technologically important inconveniences in nuclear reactors at normal service condition temperatures (low temperatures <600 K) like nucleation and growth of new phases [2] or complexions [3] and as a consequence, changes in their properties. Particularly, such diffusion process is fundamental for the development of Fe rich compounds in the alloy [4] as can affect its corrosion resistance [5] and mechanical properties. In this work we present Fe diffusion measurements made on pure zirconium: volume, B and C kinetics in grain boundaries (GB) between 368 and 600 K. The movement of fast diffusing elements (like Fe, Co, Cr, Ni) produces microstructural changes and technologically important inconveniences in nuclear reactors at normal service condition temperatures (low temperatures <600 K). In this work, volume and grain boundaries (GB) diffusion of Fe in polycrystalline high purity Zr is measured using sectioning and LIBS technique between 368 and 600 K. Diffusion profiles, diffusion kinetics, segregation factor, Arrhenius plot, diffusion mechanisms and LIBS technique are discussed and, when possible, validated with existing data.